The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1080/1356182031000122852
|View full text |Cite
|
Sign up to set email alerts
|

Physician–nurse practitioner teams in chronic disease management: the impact on costs, clinical effectiveness, and patients' perception of care

Abstract: Increasing demand to deliver and document therapeutic and preventive care sharpens the need for disease management strategies that accomplish these goals efficiently while preserving quality of care. The purpose of this study was to compare selected outcomes for a new chronic disease management program involving a nurse practitioner - physician team with those of an existing model of care. One hundred fifty-seven patients with hypertension and diabetes mellitus were randomly assigned to their primary care phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
249
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(260 citation statements)
references
References 53 publications
7
249
0
4
Order By: Relevance
“…Edwards et al (2003) 9 cliniques où les soins primaires sont assurés par les infirmières Grande qualité des soins (94% conformes aux recommandations existantes; 91% des patients très satisfaits et 94% indiquant l'intention de revenir). Litaker et al (2003) Résultats dans la gestion de maladies chroniques de patients traitées par des IPs ou des médecins (hypertension et diabète) Amélioration significative des patients concernant le contrôle de la pression artérielle et du diabète. Plus grande satisfaction des patients.…”
Section: Evaluations Dans Les Soins Primairesunclassified
See 2 more Smart Citations
“…Edwards et al (2003) 9 cliniques où les soins primaires sont assurés par les infirmières Grande qualité des soins (94% conformes aux recommandations existantes; 91% des patients très satisfaits et 94% indiquant l'intention de revenir). Litaker et al (2003) Résultats dans la gestion de maladies chroniques de patients traitées par des IPs ou des médecins (hypertension et diabète) Amélioration significative des patients concernant le contrôle de la pression artérielle et du diabète. Plus grande satisfaction des patients.…”
Section: Evaluations Dans Les Soins Primairesunclassified
“…Plusieurs études ont établi que toute économie sur les salaires des infirmières (comparés à ceux des médecins) est contrebalancée en partie ou entièrement par différents facteurs tels que des consultations plus longues, une plus grande orientation des médecins vers d'autres docteurs ou des taux plus élevés dans la réitération de consultations, et parfois la prescription de davantage de tests. Si les services impliquent des tâches complémentaires par les infirmières en pratique avancée, alors le coût peut augmenter, comme indiqué par exemple dans l'évaluation d'un programme de gestion de maladies chroniques aux Etats-Unis (Litaker et al, 2003). Cependant, ces évaluations n'ont peut-être pas pris en compte des économies potentielles liées à l'empêchement de complications graves de ces affections chroniques.…”
unclassified
See 1 more Smart Citation
“…39 As a result, justification is required to increase manpower in the department. 40 Some clinical studies have concluded that primary care teams improve outcomes at reasonable incremental costs [41][42][43] ; however, no economic evaluations on team-based solutions to decrease EDLOS have yet been reported. Given our era of limited health resources, 44 a rigorous determination of the cost-effectiveness of ED team-based solutions for LOS would help hospital administrators and decision makers decide whether implementation of a team-based approach to ED management is worth the expense.…”
Section: Introductionmentioning
confidence: 99%
“…The primary healthcare system is in need of novel care models that leverage interprofessional team members to provide alternatives to physiciancentred care. In diabetes care for example, alternative care models [5][6][7][8] have been explored as approaches outside of traditional physician-led visits [9]. Group medical visits, self-management education and group education have become increasingly popular.…”
Section: Introductionmentioning
confidence: 99%